Addressing Pronunciation Challenges in Diverse Language Classrooms - Latifah, Nur; Chai, Napat; Chai, Som (Journal International of Lingua and Technology, 2024)
Pronunciation is a critical yet challenging aspect of language learning, particularly in diverse classrooms where learners come from varied linguistic backgrounds. Mispronunciations can hinder effective communication and reduce learners' confidence. Despite its importance, pronunciation instruction is often neglected in language curricula, leaving learners ill-prepared for real-world interactions. This study addresses this gap by exploring effective strategies to tackle pronunciation challenges in multilingual classrooms. The research aims to identify the most common pronunciation difficulties faced by learners in diverse language classrooms and evaluate the effectiveness of targeted instructional strategies in addressing these challenges. A mixed-methods approach was employed, combining quantitative pre- and post-tests with qualitative classroom observations and interviews. Participants included 150 learners from diverse linguistic backgrounds enrolled in an English as a Second Language (ESL) program. Targeted pronunciation exercises, including minimal pair drills and intonation practice, were implemented over a 12-week period. Data were analyzed using statistical software and thematic analysis. The findings revealed significant improvements in learners' pronunciation accuracy, particularly in stress patterns and vowel sounds. Participants reported increased confidence in speaking and greater awareness of their pronunciation errors. Classroom observations indicated that interactive and repetitive exercises were most effective in addressing pronunciation challenges. Targeted pronunciation instruction is essential for improving communication skills in diverse language classrooms.